2014
DOI: 10.4028/www.scientific.net/amm.493.300
|View full text |Cite
|
Sign up to set email alerts
|

Production of Ethanol as a Renewable Energy by Extractive Fermentation

Abstract: One issue with batch fermentation is that product inhibition causes low yields and ethanol productivity. The objective of this study was to increase the yield and ethanol productivity via continuous fermentation in a packed bed bioreactor with both an integrated extraction process and recycling of the raffinate into the fermenter. Molasses was used as the feedstock, and the immobilized cells were supported by ĸ-carrageenan. This process used n-amyl alcohol, 1-octanol, and 1-dodecanol as solvents. The yield and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…In toxicity experiments, it was observed that longer chained alcohols have lower inhibitory effects, which is expected based on log P biocompatibility theory. Although n ‐amyl alcohol had shown higher toxicity, it allowed the highest ethanol productivity and yield, confirming better ethanol recovery values previously determined through separation assays [80]. That study showed that it is important to consider biocompatibility and extractive fermentation performance as a balance between different variables, once, as in this case, small differences in toxicity between solvents could be overcome by recovery efficiency.…”
Section: Techniques Used In Isprsupporting
confidence: 80%
See 1 more Smart Citation
“…In toxicity experiments, it was observed that longer chained alcohols have lower inhibitory effects, which is expected based on log P biocompatibility theory. Although n ‐amyl alcohol had shown higher toxicity, it allowed the highest ethanol productivity and yield, confirming better ethanol recovery values previously determined through separation assays [80]. That study showed that it is important to consider biocompatibility and extractive fermentation performance as a balance between different variables, once, as in this case, small differences in toxicity between solvents could be overcome by recovery efficiency.…”
Section: Techniques Used In Isprsupporting
confidence: 80%
“…Solvent extraction has also been effective for ethanol production as demonstrated by Widjaja and colleagues, which tested some alcohols (1‐dodecanol, 1‐octanol, and n ‐amyl alcohol) as an organic phase in Zymomonas mobilis cultivation [80]. In toxicity experiments, it was observed that longer chained alcohols have lower inhibitory effects, which is expected based on log P biocompatibility theory.…”
Section: Techniques Used In Isprmentioning
confidence: 97%
“…Avoiding yeast inhibition increases ethanol yield and process efficiency, shortens the fermentation time, and decreases the production costs. Several advanced hybrid processes for in situ bioethanol removal have been described in the literature, which combine fermentation with vacuum fermentation [190,191], flash fermentation [113,191,192], gas stripping [193,194], adsorption [195][196][197], solvent extraction [198][199][200][201][202], and membrane pervaporation [168,203,204].…”
Section: Advanced Hybrid Processesmentioning
confidence: 99%
“…It can reduce both fossil based energy source and greenhouse effect that become main environment issue nowadays. Bioethanol itself is a renewable fuel source that will not produce extra carbon dioxide from its usage and can be categorized as clean alternative energy that can be renewed (Widjaja et al, 2014).…”
Section: Introductionmentioning
confidence: 99%